Accuracy and reliability of GPS devices for measurement of movement patterns in confined spaces for court-based sports - Duffield, R.; Reid, M.; Baker, J.; Spratford, W. (Journal of Science and Medicine in Sport, 2010)
The aim of this study was to assess the accuracy and reliability of global positioning system (GPS) measures of distance and speed, compared to a high-resolution motion analysis system, for confined movement patterns used in many court-based sports. A single male participant performed 10 repetitions of four respective drills replicating court-based movement patterns and six repetitions of a random movement drill that replicated tennis match-play movement patterns. Two 1 Hz and two 5 Hz GPS devices concurrently measured distance covered and speed of all court-based drills. A 22 camera VICON motion analysis system, operating at 100 Hz, tracked the position of an 18 mm reflective marker affixed to one of the GPS devices to provide the criterion movement data. Results indicated that both 1 and 5 Hz GPS devices under reported distance covered as well as both mean and peak speed compared to the VICON system (P < 0.05). The coefficient of variation for both GPS devices for distance and speed measures ranged between 4 and 25%. Further, the faster the speed and more repetitive the movement pattern (over a similar location), the greater the measurement error. The inter-unit reliability for distance and speed measures of both 1 and 5 Hz systems for movements in confined spaces was generally low to moderate (r = 0.10-0.70). In conclusion, for court-based sports or movements in confined spaces, GPS technology under reports distance covered and both mean and peak speed of movement.